2020
DOI: 10.1002/cbic.201900739
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Protonation of Surface Carboxylate Groups in PsbO Enables Local Buffering and Triggers Structural Changes

Abstract: Photosystem II (PSII) catalyzes the splitting of water, releasing protons and dioxygen. Its highly conserved subunit PsbO extends from the oxygen‐evolving center (OEC) into the thylakoid lumen and stabilizes the catalytic Mn4CaO5 cluster. The high degree of conservation of accessible negatively charged surface residues in PsbO suggests additional functions, as local pH buffer or by affecting the flow of protons. For this discussion, we provide an experimental basis, through the determination of pKa values of w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Given the large number of carboxylate groups and net negative charge carried by protein S sequences, we sought to find out whether protein S has patches of carboxylate and histidine groups, as such patches are of potential interest for proton binding ( Bondar and Lemieux, 2019 , Checover et al, 2001 , Gerland et al, 2020 , Guerra and Bondar, 2015 , Kemmler et al, 2019 , Lorch et al, 2015 , Shutova et al, 2007 ). We found that the sequence of SARS-CoV-2 protein S has multiple positions where Asp, Glu or His groups are adjacent or separated by 1–2 amino acid residues; of the 17 His groups of the protein, 7 are within the C-terminal ~220 residue fragment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the large number of carboxylate groups and net negative charge carried by protein S sequences, we sought to find out whether protein S has patches of carboxylate and histidine groups, as such patches are of potential interest for proton binding ( Bondar and Lemieux, 2019 , Checover et al, 2001 , Gerland et al, 2020 , Guerra and Bondar, 2015 , Kemmler et al, 2019 , Lorch et al, 2015 , Shutova et al, 2007 ). We found that the sequence of SARS-CoV-2 protein S has multiple positions where Asp, Glu or His groups are adjacent or separated by 1–2 amino acid residues; of the 17 His groups of the protein, 7 are within the C-terminal ~220 residue fragment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is an additional indication for a slight expansion of dPSIIcc in buffer solution. Since the latter expansion concerns largely the membrane-extrinsic parts of PS II, it may also be caused by a larger conformational flexibility in this region of dPSIIcc. , …”
Section: Resultsmentioning
confidence: 99%
“…Oryza sativa normally grows emerged in water ( Yan et al., 2023 ), whereas Zea mays grows under more dry conditions on land. Differences in the charge distributions of Zm Chi19A and Os Chi19A may be adaptations to specific ecological niches, lifestyles, or host-pathogen interactions ( Vanhoye et al., 2004 ; Garcia-Moreno, 2009 ; Gerland et al., 2020 ; Kim et al., 2020 ; Panja et al., 2020 ; Di Savino et al., 2021 ; Doan et al., 2022 ; Vallina Estrada et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%